Golasecchiani bucket pendants in an Etruscan-Po valley context (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Forcello in Bagnolo San Vito (MN) is an Etruscan settlement situated in the middle of the Po Valley, near the Mincio and the Po river. During its life (middle of VI-beginning of IV century B.C.), it played an important role in the trade between the Mediterranean World and central Europe. Many artefacts coming from Greece and other culture like Golasecca, Venetian and transalpine once, including 34 basket-shaped pendants, typical of the female costume of the Golasecca culture. In Forcello there are almost all the types studied by R.C. de Marinis, dated to all different phases of the settlement. The pendants are important elements for defining the identity of a culture, so their presence in an Etruscan settlement could mean that some women of Golasecca culture lived here, probably because of an outbreeding practice between different cultures.
Keywords: Basket-shaped pendant; Forcello; Golasecca culture; etruscan settlement; outbreeding practice